Applications of Ordinary Differential Equations to Problems of Physics and Biology in the Geogebra Program - Agathonov A.A; Eshniyazov A.I.; Xidirova Sh.B. (Genius Journals, 2022)
The article discusses the application of the GeoGebra system of dynamic mathematics for solving ordinary differential equations underlying many physical and biological processes
Keywords: computer modeling; ordinary differential equations; GeoGebra